2022
DOI: 10.1111/bjet.13193
|View full text |Cite
|
Sign up to set email alerts
|

Linking cognitive processes and learning outcomes: The influence of cognitive presence on learning performance in MOOCs

Abstract: Massively open online courses (MOOCs) offer learners opportunities for self‐improvement and knowledge development. Linking cognitive processes and learning outcomes is helpful in supporting students learning with the help of MOOCs. Based on the cognitive presence of the Community of Inquiry framework, this study quantified the effect of cognitive presence on students’ learning performance by analysing more than 400,000 posts of 13 MOOCs. First, the study built a highly predictive classification model using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
(119 reference statements)
0
0
0
Order By: Relevance
“…The results of this investigation are consistent with the conclusions of a prior study (Fiock, 2020). In addition, this study has confirmed that cognitive presence is highly observed in blogging activities, which is similar to the findings of a previous research (Liu et al, 2022). On the contrary, several studies (Garrison, 2007;Galikyan and Admiraal, 2019) have found difficulties to move toward higher cognitive and inquiry levels in asynchronous online discussions.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this investigation are consistent with the conclusions of a prior study (Fiock, 2020). In addition, this study has confirmed that cognitive presence is highly observed in blogging activities, which is similar to the findings of a previous research (Liu et al, 2022). On the contrary, several studies (Garrison, 2007;Galikyan and Admiraal, 2019) have found difficulties to move toward higher cognitive and inquiry levels in asynchronous online discussions.…”
Section: Discussionsupporting
confidence: 92%